The Hero’s Journey of Sam Witwicky in Transformer Series - Lanny Vindiana; Liliek Soelistyo (Institute of Research and Community Outreach - Petra Christian University, 2014)
The analysis is on Sam Witwicky, an ordinary man with no any special ability that becomes a hero and saves the earth in Transformers Series. In this thesis, I will reveal the reason of how Sam Witwicky becomes a hero. I will use the theory of the hero’s journey in order to reveal the reason of Sam Witwicky’s long journey in becoming a hero. In analyzing this movie, I will analyze the stages of the hero’s journey that Sam undergoes in order to be a hero. These are his departure, initiation, and return. Meanwhile, in departure stage, there are four steps that Sam faces in order to find his identity. Next, in initiation stage I discover that Sam needs to gather his courage. Last, in the return stage, Sam needs to have wisdom.